2004
DOI: 10.1074/jbc.m401340200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the DXD Motifs in Human Xylosyltransferase I Required for Enzyme Activity

Abstract: Human xylosyltransferase I (XT-I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…XT-I Activity Assay-Using whole protein extracts from cardiac tissue or cell culture supernatant, the analysis of XT-I activity was carried out as described previously (21). The method is based on the incorporation of […”
Section: Methodsmentioning
confidence: 99%
“…XT-I Activity Assay-Using whole protein extracts from cardiac tissue or cell culture supernatant, the analysis of XT-I activity was carried out as described previously (21). The method is based on the incorporation of […”
Section: Methodsmentioning
confidence: 99%
“…In GT-A fold glycosyltransferases, which include XXTs, the DxD motif (Asp-x-Asp) plays an important role in coordinating an essential divalent cation (Busch et al, 1998;Wiggins and Munro, 1998;Zhang et al, 2001;Boeggeman and Qasba, 2002;Götting et al, 2004;Cavalier and Keegstra, 2006;Bobovská et al, 2014). Structural characterization of a putative glycosyltransferase from the Paramecium bursaria chlorella virus-1 (PBCV-1), which is predicted to belong to the same GT34 gene family as the XXTs, showed that the two Asp residues in the DxD motif participate in the coordination of the divalent cation (Zhang et al, 2007).…”
Section: Xxt5 Activity Requires the Dxd Motifmentioning
confidence: 99%
“…The DxD motif functions to coordinate the divalent cation that forms ionic interactions with the negatively charged diphosphate moiety in UDP-Xyl and is critical for catalytic activity in numerous other glycosyltransferases (Busch et al, 1998;Wiggins and Munro, 1998;Li et al, 2001;Götting et al, 2004). To determine the functional role of XXT5 in vivo, we overexpressed the XXT5 D228A:D230A mutant in the xxt5 knockout mutant plant.…”
mentioning
confidence: 99%
“…Based on experimental studies on a3ManT [52], XylT [53], GM2 synthase [54] and fringe [55], the DxD motif has been implicated in binding phosphate group and the metal ion.…”
Section: Location Of Residues Whose Functional Importance Has Been Stmentioning
confidence: 99%